De la sublimitat cortesa a l’efusió llibertina. L’altra cara de la «fin’amor» - Beltran, Vicenç (Caplletra. Revista Internacional de Filologia, 2003)
Review of satirical and obscene poetry, from the Galician/Portuguese and Provençal traditions to the «Cancionero de obras provocantes a risa» including Baena’s «Cancionero» and the «Cancionero General» by Hernando del Castillo. The author shows there is continuity in the use of these themes that is independent of their treatment and the rhetorical settings.The last pages are dedicated to the «Carajicomedia», the work of an author who is familiar with Valencia and perhaps with the milieu of Fenollar and company.